Brazilian Influences on Popular Education in Spain. The Hallmarks of Paulo Freire in Enrique de Castro's Work - Tatiane De Freitas Ermel; José Luis Hernández Huerta (Springer, 2022)
In the 1970s and 1980s, the social and professional imaginaries of education, sociopolitical conceptions of it, and educational practices in Spain, began to be influenced by certain elements specific to critical popular education, which had developed in Latin America during the long 1960s. Paulo Freire's work was particularly prominent among such influences, either directly or indirectly inspiring social and fundamental educational movements in contexts of poverty, marginalisation and social exclusion -for example, street educators. One of the most significant examples of these Freirean practices was Enrique de Castro- a working-class priest who worked in the south of Madrid (Spain) with young people in such a position, from the early 1970s. At the same time, he laboured to bring about social transformation and development; the project managed to Garner the involvement of practically the entire community. This article analyses Paulo Freire's influence in the educational and community principles expressed by Enrique de Castro in his works ¿Hay que colgarlos? and Dios es ateo. Particular attention is paid to the notions of awareness-raising, education, social action, community development, social and critical leadership of institutions, which de Castro championed.